A Cross-sectional Assessment of Health-related Quality of Life among Patients with Chronic Obstructive Pulmonary Disease - Miguel Ángel GARCIA-GORDILLO; Daniel COLLADO-MATEO; Pedro Rufino OLIVARES; José Carmelo ADSUAR; Eugenio MERELLANO-NAVARRO (Tehran University of Medical Sciences, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is a major cause of mortality characterized by progressive airflow obstruction and inflammation in the airways, which has an impact on health-related quality of life. The EQ-5D-5L is one of the most used preference-based, health-related quality of life questionnaire. The objective of this study was to provide normative values of EQ-5D-5L for Spanish people suffering from COPD. Methods: Data were extracted from the Spanish National Health Survey (2011/2012). Overall, 1130 people with COPD participated in this survey. The utility index of EQ-5D-5L and the Visual Analog Scale (VAS) score were defined by gender, region, and age. Results: Mean (SD) EQ-5D-5L utility index and VAS score for Spanish people with COPD were 0.742 (0.309) and 60.466 (21.934) respectively. In general, men reported better health status than women. Ceiling effect of the whole sample was 30.35%. Conclusion: The current study provides normative values of EQ-5D-5L for Spanish people affected by COPD. Ceiling effect was high and better results were observed in men compared with women.